Demand–supply balance of disaster medical care in Osaka City based on damage estimation for a Nankai Trough megathrust earthquake: A geographic information system‐based analysis - Hiromasa Yamamoto; Yoshinari Kimura; Kenichiro Uchida; Tetsuro Nishimura; Yasumitsu Mizobata (Acute Medicine & Surgery, 2023)
Aim Studies have not fully examined whether the medical care system would be able to manage the high number of casualties due to a Nankai Trough earthquake, whose probability of recurrence in the next 30 years is ~70%. This study assessed the demand–supply balance of the disaster medical care system in Osaka city by integrating the data on damage estimation and disaster coping hospitals using a geographic information system. Methods We obtained data on the distribution of casualties in two cases, high and low rates of evacuation from the tsunami, and available beds in Osaka city calculated from operating data of each disaster coping hospital. We expanded these data on a geographic information system and investigated the balance of medical care. Results The total number of available beds in the disaster medical care facilities was 5,559, and the shortage with evacuation rates being either low or high, would be 47,631 and 1,487, respectively. With a low evacuation rate, bed shortage is a common occurrence in coastal areas. With a high evacuation rate, bed shortage decreases, and problems with medical care arise in the eastern area of Osaka city. Discussion In the case of a low evacuation rate, greater bed shortage was found along the coast of Osaka Bay where the probabilities of flooding are high. In the case of a high evacuation rate, however, the number of casualties was much lower. A shortage of medical care did not occur along the coast, but in the eastern part of Osaka city.